A STUDY ON HIGH SCHOOL STUDENTS’ PROBLEM IN MATHEMATICS SUBJECT - Bikram Baro, Sahalad Borgoyary, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article tries to revealed about the high school students’ problem in mathematics subject. For this a data is collected through questionnaire method.A total of seven high schools of the district Baksa of Assam is purposefully selected in the survey. The questionnaire method is conducted through the response sheet in order to get the data. As the data is collected afresh, so this can be regarded as a primary data collection. why the majority of students in this particular area are poor in mathematics subject is focused in this article. Some basic problems and factors are identified and trying to well defined.Based on response sheet of the evaluated test, students’ performance is categorized into different sections. These categories are considered as a fuzzy set based on the personal category. Since the collected can be regarded as imprecise data, so the process of defuzzification is used here to convert the data into precise form. The centre of gravity (COG) or the centroid of area (COA) method is used to get the centroid of the data sets or to get the defuzzified value.